The Dilemma of the State’s Strategic Planning Subject - Diskienė, Danuta; Marčinskas, Albinas; Vakelis, Virginijus (Ekonomika, 2008)
Economic transformation and globalization not only bring changes but also emphasize the significance of the quality of strategic planning. One of the most valuable factors of the state’s strategic planning remains to be its determination. A short historical period of the independent state functioning failed to provide conditions for an integral performance of the state’s strategic planning entity elements. Only in the year 2002 the strategy of the sustainable development of economy was launched. Conversely, by present, the structure of the state performance programmes has become definite. In any case, however, the necessity of the presence of an independent national strategic research centre is imminent.The key aspect in the process of state’s strategic planning is an immaculate application of SWOT analysis, which relates, in the first place, to the harmonization of insights of the experts performing this analysis. It is purposeful establishing expert groups to evaluate their different relationship in the context of state’s governing functions. The first expert group could form (and likely be interested in) internal strategic insights, i.e. civil servants of the state’s governance structures, whereas the second group of experts, being more distracted, could present a more scientific background. And lastly, the experience of foreign counterparts involved in the related spheres of their countries would be beneficial.It would allow the possibility to create a completed rather than fragmented comparative basis. Every single aspect of state’s economic development necessitates a methodologically finalized strategic context.It is very important to legally define the subject of state’s strategic planning, the focus of which is the government. The government, however, remains liable for the independent arrangement of the state’s strategic documents. The Seimas, in its turn, seeks harmonization between the state’s development strategy and the government programme.